2020
DOI: 10.1002/advs.202001300
|View full text |Cite
|
Sign up to set email alerts
|

MeCas12a, a Highly Sensitive and Specific System for COVID‐19 Detection

Abstract: Cas12a-based systems, which detect specific nucleic acids via collateral cleavage of reporter DNA, display huge potentials for rapid diagnosis of infectious diseases. Here, the Manganese-enhanced Cas12a (MeCas12a) system is described, where manganese is used to increase the detection sensitivity up to 13-fold, enabling the detection of target RNAs as low as five copies. MeCas12a is also highly specific, and is able to distinguish between single nucleotide polymorphisms (SNPs) differing by a single nucleotide. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
81
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 107 publications
(94 citation statements)
references
References 39 publications
2
81
2
Order By: Relevance
“…They studied the crystal structure of Cas12a to form a hypothesis regarding crRNA extension and its influence on collateral cleavage activity. Interestingly, this study produced results that contradicted those of Ma et al, 2020. The authors found out Mn 2+ inhibited the LbCas12a activity, in contrast to Mg 2+ , which increased the activity. This contradiction should be further studied with the same controls to determine the reason behind the two different results.…”
Section: Cas12-effector-based Covid-19 Diagnostic Toolscontrasting
confidence: 82%
See 3 more Smart Citations
“…They studied the crystal structure of Cas12a to form a hypothesis regarding crRNA extension and its influence on collateral cleavage activity. Interestingly, this study produced results that contradicted those of Ma et al, 2020. The authors found out Mn 2+ inhibited the LbCas12a activity, in contrast to Mg 2+ , which increased the activity. This contradiction should be further studied with the same controls to determine the reason behind the two different results.…”
Section: Cas12-effector-based Covid-19 Diagnostic Toolscontrasting
confidence: 82%
“…They demonstrated that using Mn 2+ increased the efficiency and, most importantly, the specificity. Thus, they termed this technique manganeseenhanced Cas12a (MeCas12a) (Ma et al, 2020). It has been found that Mn 2+ helps to stabilize the most stable bond between CRISPR and target DNA (Sundaresan et al, 2017).…”
Section: Cas12-effector-based Covid-19 Diagnostic Toolsmentioning
confidence: 99%
See 2 more Smart Citations
“…To elevate the detection power, people have been mainly focusing on selecting better effector components (e.g., Cas nuclease, gRNA, reporter, and polymerase), adjusting the stoichiometry of different constituents (e.g., Cas protein:gRNA ratio) 19, 25 or modifying gRNA structure to augment trans-cleavage activity of Cas protein 18 . In addition to manipulating detection components, changing the reaction environment by either optimizing buffer condition (e.g., use Mn 2+ instead of Mg 2+ ) or adding chemical additives into reaction systems represent another directions to increase detection capability 25, 26 . Chemicals such as polyols, polymers, amino acid and their derivatives have been used as solvent additives to stabilize proteins and/or affect solvent properties, thereby influencing the kinetics of reaction chemistry 27 .…”
Section: Introductionmentioning
confidence: 99%